Gangguan mood pada remaja - Des Infrando; Sri Sofyani; Widiastuty dr (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Mood disorder is a psychiatric problem which arise from depression disorder. Depression case in adolescent is a strong prediction to get depression in adulthood. About 1.5-2.5% in prepuberty and become 4-5% in adolescence. During some generation, had been known that sadness and desperation also can happen in child and adolescent, but concept about mood disorder need more time to be accepted as generally.Keywords : mood disorder; adolescent